2004
DOI: 10.1097/00000542-200408000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Shock in Swine: Nitric Oxide and Potassium Sensitive Adenosine Triphosphate Channel Activation

Abstract: The data indicate that profound KATP activation associated with increased nitric oxide concentrations and inducible nitric oxide synthase induction is a key factor in vascular smooth muscle hyporeactivity characteristic of the late decompensatory phase of hemorrhagic shock in swine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In this regard, it has been shown that ATP concentration decreases in the late stage of HS and that K ATP channel activation ensues, 41,42 which could also be contributing to membrane hyperpolarization. 15,16,[43][44][45] Previous work by us and others has also shown that K ATP activation contributes to the large membrane hyperpolarization in ASMCs from shock animals 14 -16,44,45 and that K ATP inhibition by glibenclamide restores the vascular reactivity to some extent. 16 In summary, we have demonstrated an enhanced coupling efficiency between Ca 2ϩ sparks and BK Ca in ASMCs from shock animals.…”
Section: Discussionmentioning
confidence: 88%
“…In this regard, it has been shown that ATP concentration decreases in the late stage of HS and that K ATP channel activation ensues, 41,42 which could also be contributing to membrane hyperpolarization. 15,16,[43][44][45] Previous work by us and others has also shown that K ATP activation contributes to the large membrane hyperpolarization in ASMCs from shock animals 14 -16,44,45 and that K ATP inhibition by glibenclamide restores the vascular reactivity to some extent. 16 In summary, we have demonstrated an enhanced coupling efficiency between Ca 2ϩ sparks and BK Ca in ASMCs from shock animals.…”
Section: Discussionmentioning
confidence: 88%
“…[17] The physiological antagonism between nitric oxide and angiotensin II, which has already been demonstrated in rats [18] and later in pigs, shows an association between activated K + ATP channels and nitric oxide. [19] The recovery of mean arterial blood pressure in hemorrhagic shock treated with K + ATP channel inhibitors has already been reported in rats [20] but was not seen under the acute conditions of this study.…”
Section: Discussionmentioning
confidence: 45%
“…The mechanism of action is not well understood but may result from inactivation of K ϩ currents that normally develop in vascular smooth muscle cells during metabolic acidosis (18). Reversal of these K ϩ currents has been suggested as a means by which vascular sensitivity to catecholamines is reestablished by AVP infusion in decompensated shock (25). In the present study, drug intervention was begun prior to decompensation.…”
Section: Discussionmentioning
confidence: 91%